Payment Gateways, Green Financing, and Sustainability Innovation in Islamic Economics for MSMEs and SDGs - Dian Rahmawati, Sisca; Nur Rahmawati; Moenawar Kholil; Permatasari, Qisthoni; Yuliana Subastine; Mohammad Firdaus Mohammad Hatta (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to examine the integration of payment gateways, green financing, and sustainability innovation in improving MSME performance, while exploring their contribution to the achievement of the United Nations Sustainable Development Goals (SDGs), particularly those related to inclusive economic growth and sustainable business practices. Theoretical framework: This research is grounded in the perspective of sustainable development and digital financial innovation, which views digital payment systems, environmentally responsible financing, and sustainability-driven innovation as key elements in enhancing MSME competitiveness and resilience. This framework is linked to the SDGs agenda, particularly goals related to decent work and economic growth, responsible consumption and production, and partnerships for sustainable development. Literature review: Previous studies have highlighted the important role of digital financial technology in improving transaction efficiency and financial inclusion for MSMEs. Other studies emphasize the significance of green financing in supporting environmentally responsible business activities, as well as the role of sustainability innovation in strengthening business competitiveness and long-term resilience in the global economy. Method: This study employs a quantitative research approach using survey data collected from MSME owners and managers. The analysis focuses on examining the relationships between payment gateway adoption, green financing access, sustainability innovation, and MSME performance through statistical modeling techniques to obtain a comprehensive understanding of the proposed research model. Results: The findings indicate that payment gateway adoption, green financing, and sustainability innovation positively influence MSME performance. Digital payment systems improve transaction efficiency and market accessibility, green financing supports environmentally sustainable business investments, and sustainability innovation enhances product competitiveness and long-term business sustainability. These elements collectively contribute to strengthening MSME development in line with the SDGs agenda. Therefore, integrating digital financial technology, green financing, and sustainability innovation within an Islamic economic framework may provide a holistic approach to improving MSME performance. Implications: This research highlights the importance of integrating digital financial technology, sustainable financing, and innovation in MSME development strategies. The findings also support policy initiatives aimed at improving digital infrastructure, expanding access to green financing, and promoting sustainability-oriented business practices to strengthen MSME competitiveness while supporting the SDGs agenda. Novelty: The novelty of this study lies in the integration of payment gateways, green financing, and sustainability innovation within a comprehensive analytical framework to examine their combined impact on MSME performance while linking MSME development with the achievement of the United Nations Sustainable Development Goals.